Cultivation of Digital Literacy Culture Through an Interest in Reading Literature 21st Century Life Skills - Wulan Handayani; Diena San Fauziya (JLER (Journal of Language Education Research), 2023)
This study aims to photograph or measure the culture of digital literacy in early adolescents, around 11-14 years or junior high school level. This research was conducted on students of SMP Pahlawan Toha Bandung, totaling 40 students. The research was conducted by surveying the understanding and ability to use digital devices, as well as students' interest in reading literature through the devices they have. The research method used is quantitative descriptive, the research subjects are students of SMP Pahlawan Toha Bandung, and the object of research is survey data on the level of digital literacy culture among students. The instrument used is in the form of a questionnaire compiled through the media Google form which is distributed to students, then proceed with coding data, tabulating, scoring, and data analysis to conclude. The study results show a cultural portrait of early adolescent digital literacy at SMP Pahlawan Toha Bandung, which is known to be going well and has become entrenched, shown by 95% of students being able to use technology and information media tools properly, and ethically. Even so, having digital literacy competence will not always automatically increase interest in reading or writing literacy, let alone interest in literary literacy. Efforts are needed to ensure that the better students use digital media as a tool to help, make it easier to access literacy materials, and obtain general and specific information related to literary works, the better will be the achievement of student life skills competencies in the 21st century.